Higher order thinking skills integration into the teaching of literary texts: a mooc for English language teachers - Mat Daud, Nuraihan; Mat Daud, Nor Shidrah; Mohamad Ali, Afiza; Juhary, Jowati; Mohd Mydin, Raihanah (IATED Academy, 2017)
Higher Order Thinking Skills (HOTS) are among the skills that teachers at school are expected to develop. In a language class, this can be a challenging task especially for teachers who are not trained in this area. Yet, many may not opt for a formal face-to-face training for various reasons. Time is usually one of the constraints. In-service training programmes are also impossible to arrange for all teachers in the country. In a survey conducted on English teachers in Malaysia, it was found that they preferred to have this kind of training conducted both on-site and online. Majority of them preferred to have the bulk of the course to be run online. This paper discusses the strategies and approaches that can be adopted by English language teachers to develop their students’ critical thinking skills when teaching literary texts. The paper also highlights how these are shared with the teachers using MOOC platform. The platform helps to make the content accessible to more teachers. keywords: hots, language teaching, mooc.